Cannabidiol for the Management of Endometriosis and Chronic Pelvic Pain. Issue 3 (March 2022) - Mistry, Megha; Simpson, Paul; Morris, Edward; Fritz, Ann-Katrin; Karavadra, Babu; Lennox, Carole; Prosser-Snelling, Ed
Abstract : (Abstracted from J Minim Invasive Gynecol 2022;29:169–176) Current treatments for women with endometriosis are largely ineffective for management of pain and other symptoms. In addition, they often affect fertility and can have undesirable adverse effects that impede the long-term management of the condition.